2019
DOI: 10.1115/1.4044710
|View full text |Cite
|
Sign up to set email alerts
|

Conditions for Wall Thickness Reduction in Hollow Sinking of SUS304 Tubes With Drawing Speed Control in Entrance and Exit Sides of Die

Abstract: In this study, the conditions for wall thickness reduction in hollow sinking were obtained by tube drawing experiments in which the drawing speed ratio was controlled under three conditions (1.09, 1.11, and 1.14). These conditions have not been found in the history of hollow sinking. The results of the experiment and the theoretical formulas indicate that the geometric condition is obtained from the figure of the ratio of inner diameter to outer diameter after drawing against that ratio before drawing. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Assuming that the strain is small and the lattice rotations are negligible, the grain deformation can be calculated using strain transformation [9]. Equation (2) shows the strain when a slip system , (hkl)[uvw] is active. The parameter   is the slip strain.…”
Section: Table 2 Slip Systems Of a Fcc Metalmentioning
confidence: 99%
See 1 more Smart Citation
“…Assuming that the strain is small and the lattice rotations are negligible, the grain deformation can be calculated using strain transformation [9]. Equation (2) shows the strain when a slip system , (hkl)[uvw] is active. The parameter   is the slip strain.…”
Section: Table 2 Slip Systems Of a Fcc Metalmentioning
confidence: 99%
“…In conventional hollow sinking, the increase in wall thickness was unavoidable. However, Kishimoto et al proposed a method to control the drawing speed ratio at the entrance and exit side of the die, which enabled the hollow sinking of micro metal tubes without increasing the wall thickness [2]. Thus, hollow sinking process is suitable for the manufacturing of small-diameter tubes because it does not require an inner tool.…”
Section: Introductionmentioning
confidence: 99%
“…The outer diameter during drawing D total was calculated using Equation (6). The excessive thinning of the outer diameter during drawing η' was calculated using Equation (7). Furthermore, the excessive thinning of the outer diameter after drawing η was calculated using Equation (8).…”
Section: Excessive Thinning Of the Outer Diameter During Drawingmentioning
confidence: 99%
“…However, a contemporary drawing machine that controls both the drawing speeds on the die's entrance and exit sides has recently been developed [6]. Previously, the authors investigated the conditions for wall thickness reduction by using this machine [7]. The results demonstrated that the wall thickness could be decreased when the drawing speed ratio was larger than a threshold value, which was obtained from the die reduction and the starting dimensions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation